2022
DOI: 10.1186/s12889-022-12553-x
|View full text |Cite
|
Sign up to set email alerts
|

Research on grandchild care and depression of chinese older adults based on CHARLS2018: the mediating role of intergenerational support from children

Abstract: Background There may be differences in gender and marital status in the impact of grandchild care on the depression of the Chinese older adults. This research explores the effect of grandchild care on the depression of Chinese older adults of different genders and marital status, and explores the mediating role of intergenerational support from children between grandchild care and depression. Methods This research uses the data of 3540 Chinese olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 37 publications
5
24
0
Order By: Relevance
“…Our nding was consistent with a study which demonstrated that higher frequency engaged in social interaction with lower risk of cognitive decline [35]. As well as consistent with some studies showed that providing grandchildren care could reduce the depressive symptoms [17,30,36] and improve the cognitive function of the older adults [7,8,10]. A cohort study showed that depression was a risk factor of dementia [37].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our nding was consistent with a study which demonstrated that higher frequency engaged in social interaction with lower risk of cognitive decline [35]. As well as consistent with some studies showed that providing grandchildren care could reduce the depressive symptoms [17,30,36] and improve the cognitive function of the older adults [7,8,10]. A cohort study showed that depression was a risk factor of dementia [37].…”
Section: Discussionsupporting
confidence: 91%
“…There was 40.8% middle-aged and elderly people provided varying degrees of intergenerational care. The result of this study was similar to those of the studies conducted in CLASS 2014 [14] and another study [30]. This trend is due to China's traditional culture and the concept of lial piety, the grandparent has moral responsibility for his children and grandchildren [31].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, according to the research by Fingerman ( 16 ), excessive intergenerational economic support could damage the self-esteem of the elderly, making them feel powerless and thus damaging their mental health. Tang et al ( 17 ) found that intergenerational care support could enable the elderly to get good care, alleviate diseases, and help maintain good health. Other studies have shown that the influence of intergenerational care support on the mental health of the elderly is not insignificant ( 18 ) and even harmful ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…The National Baseline field survey was launched in 2011 and included approximately 10,000 households and 17,500 people in 150 districts and 450 village/residential councils who were followed up every two years, with all data made public one year after the end of data collection [25]. The CHARLS can provide a wealth of information when studying the health and pension issues of the elderly population in China, including basic information of respondents, health status, cognition and depression, medical care and insurance, work and retirement [26]. The CHARLS database has good reliability and validity and can better reflect the actual situation of the elderly population in China [25].…”
Section: Data Sourcesmentioning
confidence: 99%